Seismic Behaviour of Reinforced Concrete Frames with Concentric Steel Bracing: A Review of Research from 1990 to 2023 - Birendra Kumar Bohara; Prasenjit Saha (Momentum International Journal of Civil Engineering (MIJCE), 2026)
Reinforced concrete (RC) buildings strengthened with concentric steel bracing systems have been widely investigated as an effective strategy for enhancing seismic resistance in both existing and newly designed structures. However, existing studies are dispersed across various bracing configurations, design methodologies, and performance evaluation approaches, making it difficult to establish a comprehensive understanding of their seismic behavior. This study presents a systematic review of approximately 75 published studies from 1990 to 2023 retrieved from major scientific databases including Scopus, Web of Science, ScienceDirect, and Google Scholar. The reviewed literature was screened based on relevance to concentric steel-braced RC frames, seismic retrofitting, structural design, and seismic performance assessment. The findings indicate that X-bracing, Chevron bracing, and Buckling-Restrained Braces (BRBs) significantly improve lateral stiffness, energy dissipation capacity, ductility, and overall seismic performance. Experimental and numerical studies consistently report substantial reductions in inter-story drift and enhanced structural resilience under seismic loading. Recent developments involving performance-based seismic design, self-centering systems, hysteretic dampers, and computational optimization techniques have further expanded the applicability of braced RC systems. Nevertheless, challenges remain regarding standardized response modification factor evaluation, performance-based design implementation, and high-rise applications. The review highlights current research trends, identifies critical knowledge gaps, and provides recommendations for future investigations involving advanced materials, hybrid systems, and artificial intelligence-based structural optimization.